Smartphone usage motives and academic performances among undergraduates in University Putra Malaysia - Anumudu, Chinedu Eugenia; Adzharuddin, Nor Azura; Yasin, Megat Al Imran (Research Publish Journals, 2018)
This article generally explored factors that influenced smartphone usage motives and academic performances among undergraduates in the Faculty of Modern Language and Communication, University Putra Malaysia. Usage of smartphone facilities towards learning goal was also another possible factor considered since it seemed little or no consideration has been given to using the facilities for learning goals. Furthermore, smartphone usage pattern was also examined in this project paper. Quantitative data was collected through survey questionnaire, which was administered to 303 respondents in four departments of Modern Language and Communication Faculty via simple random sampling technique. Regarding the result, the first hypothesis outcome showed no significant relationship between smartphone cognitive need and academic performances. While the second hypothesis, showed a significant positive relationship between smartphone personal integrative need and academic performances. In the usage of smartphone facilities for learning goal, it showed that greater numbers of them utilized smartphone facilities such as Web Browser, Email and Short Message Service (SMS) as learning facilities, though Web Browser was identified as the most smartphone facility used for leaning goal. In terms of usage patterns, the result affirmed that the respondents chose patterns that were considered most appropriate to them.